2001
DOI: 10.1038/labinvest.3780240
|View full text |Cite
|
Sign up to set email alerts
|

Differential and Mutually Exclusive Expression of CD95 and CD95 Ligand in Epithelia of Normal Pancreas and Chronic Pancreatitis

Abstract: SUMMARY:Acinar regression in chronic pancreatitis may be due to immune attack in parenchymal areas neoexpressing HLA-DR molecules. CD4 ϩ Th1 cytotoxic T cells induce apoptosis of their targets via oligomerizing CD95 (APO-1/Fas) death receptors on target cells by their CD95 ligand (CD95L). We determined the expression of CD95 and CD95L in epithelia of normal and chronically inflamed pancreatic tissues. We applied RT-PCR and Western blotting for CD95L expression profiles, serial frozen section immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Summarizing our previous findings 3,4 and integrating our new data, we propose the following model of CP leading to enforced death of exocrine cells and at the same time to armored survival of endocrine cells ( Figure 5). Initiated by IFNg locally released by CD4 þ Th1 cells, exocrine pancreatic epithelia lose CD95L and neoexpress the functional death receptors CD95, TRAIL-R1 and TRAIL-R2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarizing our previous findings 3,4 and integrating our new data, we propose the following model of CP leading to enforced death of exocrine cells and at the same time to armored survival of endocrine cells ( Figure 5). Initiated by IFNg locally released by CD4 þ Th1 cells, exocrine pancreatic epithelia lose CD95L and neoexpress the functional death receptors CD95, TRAIL-R1 and TRAIL-R2.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that islets express the deathinducing ligand CD95L (FasL) but do not express its receptor CD95 (Fas). In CP, this 'immunoprivileged' status is preserved in endocrine cells, whereas the exocrine epithelia neoexpress CD95 (Fas) along with HLA-DR. 3 We further showed that islet cells in normal pancreas (NP) are devoid of TRAIL (tumor necrosis factor (TNF)-related apoptosis-inducing ligand) receptors (R), which, like CD95, are members of the TNF receptor superfamily. In CP, there is an induction and high levels of expression of TRAIL-R1, -R2 and -R4 in exocrine cells.…”
mentioning
confidence: 99%
“…In CP, TRAIL is induced in scattered exocrine epithelia and pancreatic stellate cells (PSC). Furthermore, TRAIL expression in cultured human PSC is significantly increased by IFN-␥, a potential inflammatory cytokine that we have previously shown to be present at elevated tissue levels in CP (Hasel et al, 2001).…”
mentioning
confidence: 92%
“…IFN-␥ and TNF-␣ enhanced TRAIL-R2 mRNA expression in a panel of cancers (Meng and el Deiry, 2001). In CP, tissue concentration of IFN-␥ is increased compared with NP (Hasel et al, 2001). Its most likely source seems to be the lymphohistiocytic infiltrate, which mainly consists of CD3 ϩ CD4 ϩ T cells and CD11c ϩ , CD4 ϩ/Ϫ , S100p ϩ dendritic cells (Hasel et al, 2001).…”
Section: Hasel Et Almentioning
confidence: 99%
See 1 more Smart Citation